Effect of Aspirin and Dipyridamole on the Interaction of Human Platelets with Sub-Endothelium: Studies Using Citrated and Native Blood - Weiss, Harvey J; Turitto, Vincent T; Vicic, William J; Baumgartner, Hans R (Thrombosis and Haemostasis, 1981)
The effect of aspirin and dipyridamole ingestion on the interaction of platelets with the subendothelium was studied using both citrated blood and directly sampled (native) blood. After obtained control studies, normal human subjects ingested 0.6 g of aspirin, 150 mg of dipyridamole, or a placebo and studies were repeated 1½ hrs later. Subjects continued on placebo, aspirin (0.6 g b.i.d.) or dipyridamole (100 mg q.i.d.) for 6 days and studies were obtained 1½ hrs after the last dose. Blood was circulated through an annular chamber on whose inner core were mounted everted segments of de-endothelialized rabbit aorta. The wall shear rate was 2,600 sec-1. Surface coverage with adherent platelets and platelet thrombi, as well as several parameters of thrombus dimensions, were evaluated morphometrically. Aspirin ingestion markedly reduced platelet thrombi in citrated blood, – but had a much lesser inhibitory effect in native blood. Platelet adhesion was unaffected in native blood; it was slightly decreased in citrated blood, in contrast to previous findings in which a lower shear rate (800 sec-1) was used. Ingestion of dipyridamole did not inhibit platelet adhesion or thrombi in either citrated or native blood. The studies indicate that, with the flow conditions used, aspirin is a relatively weak inhibitor of platelet thrombus formation in directly sampled human blood.
Keywords: Acetylsalicylic acid; Dipyridamole; Platelet adhesion; Platelet-subendothelium interaction